PULAU GALANG SEBAGAI PENAMPUNGAN PENGUNGSI VIETNAM - Bunari Bunari Bunari (Program Studi Pendidikan Sejarah - Universitas Samudra, 2017)
Galang Island known in the past Royal Malay (Kerajaan Melayu) as the hiding place of the Lanon (Pirates) also a topic of discussion of the international community when the United Nation High Commissioner For Refugees (UNHCR) placement of refugees